Microelectronics - Millman, Jacob 1911- (McGraw-Hill series in electrical engineering. Electronics and electronic circuits, 1987)
Providing practical information, this book coordinates the physical understanding of electronics with a theoretical and mathematical basis. With pedagogical use of second color, it covers devices in one place so that circuit characteristics are developed early.